Uma contribuição ao processo de disseminação da contabilidade internacional através do Comitê de Pronunciamentos Contábeis (CPC) - Rego, Luis Carlos do (2010)
The International Accounting is the effect created by the economic opening, result of the globalization of the markets and has as end help to eliminate the countable obstacles between the countries, being allowed the free circulation of goods and services, where all the actors have equality of conditions, keeping the balance between internal practices accountants according to their particular characteristics and the international practices accountants. The necessity of analysis of the involvements of the International Accounting is increasing, of studies of the difficulties derived from this subject, aiming to consider the possible ways in which must direct the International Accounting. In which is important to consider these appreciations in order to get the adequate tools so that the countable profession does not continue mainly with a static development in the underdeveloped countries. The harmonization of the international norms of accounting with the norms applied in Brazil is a continuous work and of primary responsibility of the CPC- Committee of Countable Uprisings